2015
DOI: 10.18632/oncotarget.3364
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 turnover and expression of ATRX determine the choice between quiescence and senescence in response to CDK4 inhibition

Abstract: CDK4 inhibitors (CDK4i) earned Breakthrough Therapy Designation from the FDA last year and are entering phase III clinical trials in several cancers. However, not all tumors respond favorably to these drugs. CDK4 activity is critical for progression through G1 phase and into the mitotic cell cycle. Inhibiting this kinase induces Rb-positive cells to exit the cell cycle into either a quiescent or senescent state. In this report, using well-differentiated and dedifferentiated liposarcoma (WD/DDLS) cell lines, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 80 publications
3
97
0
Order By: Relevance
“…Recurrent deletions (Figure 4A) included ATRX (10% deep; 20% shallow), NF1 (6% deep; 22% shallow), and CDKN2A (2% deep; 42% shallow). Given that ATRX may be required for response to CDK4 inhibitors (Kovatcheva et al, 2015) and 30% of DDLPS have ATRX deletions, ATRX alterations may represent an important correlative biomarker in future clinical trials of CDK4 inhibitors in DDLPS.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent deletions (Figure 4A) included ATRX (10% deep; 20% shallow), NF1 (6% deep; 22% shallow), and CDKN2A (2% deep; 42% shallow). Given that ATRX may be required for response to CDK4 inhibitors (Kovatcheva et al, 2015) and 30% of DDLPS have ATRX deletions, ATRX alterations may represent an important correlative biomarker in future clinical trials of CDK4 inhibitors in DDLPS.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in other tumour types have shown that palbociclib can induce cellular senescence, [40][41][42][43] which is an irreversible cell cycle arrest. 16 In HCC cells, we observed a reversible cell cycle arrest in most of the cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In an intriguing study (80), palbociclib treatment of seven RB-positive liposarcoma cell lines, each with chromosome 12q14 amplification of linked CDK4 and MDM2, arrested in a G1 state within 48 hours of drug exposure. Three of the cell lines subsequently expressed several senescence biomarkers and failed to resume proliferation when palbociclib was withdrawn.…”
Section: Palbociclib Clinical Developmentmentioning
confidence: 99%